PENINGKATAN PENGETAHUAN MASYARAKAT NAGARI MUNGKA KABUPATEN LIMA PULUH KOTA MENGENAI PENGGUNAAN OBAT - Elidahanum Husni; Rima Jumeini Cahayu (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2019)
Medicine is a substance that can be used to cure diseases. Behind its benefits, drugs can turn into poisons if not used correctly and adequately. Many people who do not know how to get, use, store and dispose of the right medicine so that counseling is needed to understand this and prevent/minimize the occurrence of side effects and toxic effects of the drug. Nagari Mungka people also do much self-medication before deciding to go to a doctor or a health center. To be able to carry out self-medication correctly, the public must get accurate information so that they can determine the type and amount of drugs needed. To protect the public from the dangers of using drugs that are not appropriate and incorrect, it is necessary to be given socialization about medication access-usage-storage-disposal education and its application in everyday life. Education about Medication access-usage-storage-disposal was conducted to the community of Nagari Mungka in Lima Puluh Kota District in July 2019, attended by 16 participants. The material provided includes how to medication access-usage-storage-disposal the right medicine and through education methods. The counseling that has been done has succeeded in increasing the Nagari Mungka community's knowledge about the types of drugs on the market, various types of drug preparations, how to use drugs, to store and dispose of expired drugs.